Perdebatan Penerapan Syariat Islam Sebagai Gerakan Politisasi Dakwah: Studi Kasus Qonun Syariah di Aceh - Susanti Hasibuan (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
Islamic Sharia is a reflection of contemporary da'wah. Islamic Sharia includes components of bilyadi da'wah by using Islam as a reference in the formation of laws covered by Islamic Sharia. religious aspects are carefully reduced and accommodated by the state constitution. The state has an important role as social control over every behavior of the community and this is legalized through the Qanun Syariat Islam in Aceh. Along with that, the current political format is affiliated with Islamic sharia. because Islamic politics was previously considered a forum for efforts to implement Islamic teachings in state life. Meanwhile, the Islamic Sharia Qanun in Aceh is already more complex in its implementation and its scope even exceeds what Islamic politics can do.